Evaluation of Skin Lesions due to Laser Hair Removal in Terms of Malpractice - Kar, Hakan; Dokgöz, Halis; Gamsız Bilgin, Nursel; Albayrak, Betül; Kaya, Tamer İrfan (The Bulletin of Legal Medicine, 2016)
Abstract Objective: Ruby, alexandrite, diode and neodymium: yttrium-aluminum-garnet (Nd: YAG) laser devices are often used for hair removal all over the world. The mechanism of laser hair removal is targeting melanin in the hair follicle by millisecond pulse durations to generate selective photothermolysis of the hair follicle. Laser application can cause skin burns, thin epidermal incrustation, hyperpigmentation, hypopigmentation and even can lead to scarring as a side effect especially in dark skin types. Therefore, the selection of the appropriate wavelength laser source according to skin types is considered a prerequisite for pre- venting undesired skin lesions. The legislation of laser hair removal is very controversial situation in our country as well as all over the world. We aimed the to reveal problems that may be encountered in the evaluation of the developed skin lesions due to laser hair removal in terms of malpractice cases and also in the reporting process and intend to suggest some solutions in current study. Materials and Methods: 14 cases with dermal lesions due to laser hair removal who were sent to Mersin University Medical Faculty Department of Forensic Medicine for forensic reporting were evaluated retrospectively for malpractice claim by means of socio-demographic features, findings of examinations and consultations, results of forensic reports, applicator person and place of application and legal statuses between 2006 -2016. Results: 12 of 14 patients were woman and the average age was found 31.21 ± 8.52 who sent for forensic reporting between 2006 and 2016. It was found to be most common in the 25-29 age and 40-44 age groups. Most of the cases made complain within the first few days of the application or after 1-2 years. The most common lesions were found to be, hyperpigmentation (n = 7), hypopigmentation (n = 5), scarring (n = 3) respectively. Face was the most common localization with 8 cases and lower extremities were the second with 5 cases. Dermatology consultation has been requested for 9 cases, 8 cases of them replied as “the detected lesions were complications related to laser application”. Laser applications were applied in “Beauty and the Esthetic Centers” by “Estheticians” in 12 cases, in “Pay Hospitals” again by “Estheticians” but in doctor’s supervision in the other two cases. Conclusion: We think that laser epilation is a medical application and should absolutely be applied by educated medical practitioner or expert or educated health care personnel in doctor’s supervision and exactly in health institutions.